Urinary Calprotectin for Early Detection of Pediatric Acute Kidney Injury: A Systematic Review and Meta-analysis - Mohammad Mehdi Hashemi; Ayda Dadras; Amirmohammad Toloui; Mohammad Kiah; Behnaz Bazargani; Neamatollah Ataei; Hamzah Adel Ramawad; Mahmoud Yousefifard; Mostafa Hosseini (Journal of Pediatrics Review)
Background: The available evidence suggests that urinary calprotectin may be a potential biomarker in distinguishing between intrinsic acute kidney injury (AKI) and prerenal AKI. Objectives: The aim of this study was to determine the diagnostic value of calprotectin in identifying pediatric acute renal impairment. Methods: A search of the Medline, Embase, Scopus and Web of Science electronic databases was conducted on April 27, 2024. Diagnostic studies conducted on the value of urinary calprotectin in AKI were included. Two independent reviewers assessed the search records and any disagreements were resolved by discussion. The risk of bias was assessed using quality assessment of diagnostic accuracy studies (QUADAS-2) guidelines. The performance of urinary calprotectin in diagnosing AKI and its discriminatory ability between intrinsic and prerenal AKI were evaluated by calculating the pooled standardized mean difference (SMD) and 95% confidence interval (CI), as well as sensitivity, specificity and area under the curve (AUC). Results: Seven studies were included. The mean urinary levels of calprotectin in AKI were significantly higher than those in the non-AKI group (SMD=0.73; 95% CI, 0.50%, 0.97%; I2=0.00%). The mean urinary levels of calprotectin in pediatrics with intrinsic AKI were significantly higher than in those with prerenal AKI (SMD=0.76; 95% CI, 0.48%, 1.05%; 95% CI, 0%). Urinary calprotectin exhibited a sensitivity of 0.937 (95% CI, 0.829%, 0.978%) and a specificity of 0.252 (95% CI, 0.126%, 0.442%) for distinguishing intrinsic AKI from prerenal AKI. Additionally, the AUC of urinary calprotectin in differentiating intrinsic AKI from prerenal AKI was 0.691 (95% CI, 0.541%, 0.809%). Conclusions: Urinary calprotectin demonstrates fair screening performance characteristics for differentiating intrinsic from prerenal AKI in children. However, the low specificity necessitates additional diagnostic testing in cases with positive results.